Wildlife Trade for Belief-Based Use: Insights From Traditional Healers in South Africa - Green, Jennah; Hankinson, Pippa; de Waal, Louise; Coulthard, Emma; Norrey, John; Megson, David; D’Cruze, Neil (Frontiers in Ecology and Evolution, 2022)
The use of animals and plants as traditional remedies for medical purposes has a long history of socio-cultural and economic importance in South Africa. Herein, we aim to characterise the social and economic value of wild animal species used in traditional medicine within South Africa from traditional healers’ perspective and to explore healers’ knowledge of plant-based alternatives to wildlife-based derivatives for this type of trade. Through structured surveys with five traditional medicine healers, we sought to gain insight into the range of wild animal species used, as well as the purpose, the perceived commercial value and the perceived availability of commonly used species. Additional focus was placed on exploring the socio-economic value of lions due to their prominence within the traditional medicine market, both in South Africa and internationally. Three of the respondents interviewed had been generating an income from traditional healing for between 30 and 50 years, and the overall monetary gain across all respondents was between ZAR 30,000 (1,800 USD) and 120,000 (7,200 USD) per annum. Our study confirms that a wide range of wild animal species are used in traditional healing practises in South Africa, for both medicinal and spiritual purposes. Respondents cited 20 common wild animals from a range of vertebrate classes including birds, reptiles, mammals, and one invertebrate. These included a number of species listed as threatened on the IUCN Red List of Threatened Species. Traditional healers cited 32 different uses for wild animal parts, as well as 19 alternative plant-based preparations. For lions specifically, four out of five practitioners listed lions among their top three profitable derivatives and three practitioners reported that lion had become the most rare or unavailable species in the last five years. Although our study is based on a limited` number of interview participants, we believe that our findings provide valuable initial insights into the socio-economic drivers of traditional healing practises in South Africa, and that further research quantifying medicinal and belief-based use of wild animal ingredients and their plant-based alternatives could help to inform approaches to managing related pressures exerted on wild populations in South Africa in the future.